Biomimetic preparation of core‐shell structured surface‐enhanced Raman scattering substrate with antifouling ability, good stability, and reliable quantitative capability. Issue 16 (4th August 2019) - Chen, Na; Meng, Xinyu; Ding, Pan; Su, Yuanyuan; Wang, Houyu; He, Yao
Abstract: The fouling and stability are two most critical limiting factors for practical applications of surface‐enhanced Raman scattering (SERS)‐based microfluidic electrophoresis device. Herein, we present a novel biomimetic nanoengineering strategy to achieve a SERS substrate featuring antifouling ability, good stability, and reliable quantitative capability. Typically, by employing tea polyphenol as the reducing agent, the substrate made of silver core‐gold shell nanostructures in situ grown on silicon wafer surface is fabricated. The core‐shell nanostructures are further embedded with internal standard molecules. Remarkably, the fabricated substrate preserves distinct SERS effects, adaptable reproducibility, and reliable quantitative ability even if the substrate is incubated with 15% H2 O2, 13% HNO3, or 10 8  CFU/mL bacteria, or suffered from 12‐day continuous vibration at 250 rpm/min in PBS buffer. As a proof‐of‐concept application, the DNA‐functionalized substrate is capable of precise quantification of Hg 2+ with a limit of detection down to ca. 1 pM even in sewage water.